Effectiveness of self-training using the mobile-based virtual reality program in patients with social anxiety disorder. (August 2017) - Kim, Hesun Erin; Hong, Yeon-Ju; Kim, Min-Kyeong; Jung, Young Hoon; Kyeong, Sunghyon; Kim, Jae-Jin
Abstract: Social anxiety is one of the common mental problems with relatively low treatment-seeking rate. Virtual reality exposure therapy is a promising treatment option for social anxiety disorder (SAD). Our objective was to investigate the efficacy of self-training using the newly developed mobile-based virtual reality program for the cost-effective treatment of SAD. Twenty-two patients with SAD and 30 sex- and age-matched normal controls engaged in the program, which consisted of eight self-training sessions during two weeks. Liebowitz Social Anxiety Scale (LSAS) was assessed before and after the training. Additionally, the embedded in-app performance variables were analyzed for objective performance improvements. Although the LSAS scores decreased after the training in both groups, patients showed greater degree of decrease at the marginal significance level than controls ( p  = 0.053). Overall, there were significant improvements in the total speech length ( p  < 0.001), voiced-time ratio ( p  < 0.001), and subjective self-ratings on the performance measured within the program for subjective nervousness ( p  < 0.001) and for the subjective confidence in content ( p  = 0.039). The findings provide compelling evidence that the self-training could be beneficial for reducing anxiety and improving skills. The mobile-based virtual reality program for the treatment of SAD may be the first mobile application treatment option that could be operated by the patient alone, at home. Highlights: Mobile-based virtual reality self-training for social anxiety was developed. The mobile program attenuated social anxiety. Through the program, participants were able to improve performance skills.